2009
DOI: 10.1111/j.1365-2028.2008.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spring water quality and quantity, and health implications in Tongaren division, Nzoia River catchment, Kenya

Abstract: Spring water is the common source of public water supply in most rural communities of developing countries such as Kenya. The water quality and quantity may be altered due to catchments degradation. This study was carried out in Tongaren division, Nzoia River catchment. The aim of this study was to investigate and map the occurrence and distribution of springs and to determine their water quality and quantity. This study determined the spring water discharge, conductivity, turbidity, total and thermotolerant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A study in Kenya revealed that total coliform was abundant in most of the spring water sources studied including protected springs, whereas fecal coliform was present in 29% of spring water sources. The authors noted that the presence of coliform may pose a high risk of water-borne diarrhea diseases (Simiyu et al 2009 ). A study on the effect of improved water supplies on U5 diarrhea prevalence showed that improved water supply reduced diarrhea in U5 children by only 11% (Cha et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Kenya revealed that total coliform was abundant in most of the spring water sources studied including protected springs, whereas fecal coliform was present in 29% of spring water sources. The authors noted that the presence of coliform may pose a high risk of water-borne diarrhea diseases (Simiyu et al 2009 ). A study on the effect of improved water supplies on U5 diarrhea prevalence showed that improved water supply reduced diarrhea in U5 children by only 11% (Cha et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Spring water is usually safe from contaminants (i.e. pathogens, chemicals, metals); since groundwater is naturally filtered as it flows through the soil (Simiyu et al, 2009). Hence, spring water is generally safe for human consumption (Hawley, 2003).…”
mentioning
confidence: 99%
“…Hence, spring water is generally safe for human consumption (Hawley, 2003). Spring water quality may be altered due to exposure to metallic elements (Marcovecchio et al, 2007;Simiyu et al, 2009). The term ''heavy metals'' refers to any metallic element that has relatively high density and applies to the group of metals and metalloids with atomic density greater than 5 g/cm 3 (Oveset al, 2012).…”
mentioning
confidence: 99%
“…Water is the basic need of all and essential for sustaining basic human functions, health and food production. Along with this, it helps in various activities, like digestion of food, adsorption, transportation and removal of toxins and wastes from the body [4]. Humans cannot produce this inevitable element of life and as the life relies on water, the quality of water becomes one of the very essential aspects in order to make it pollution free so that various water sources (ground water, surface water) can be protected.…”
Section: Introductionmentioning
confidence: 99%